Pengaruh Jumlah Kasus Covid-19 terhadap Harga Saham dan Profitabilitas pada Perusahaan Indeks LQ45 - Sucayono, Sucayono (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
The Covid-19 outbreak in Indonesia has had many negative impacts on the national economy. Many sectors have been affected by the emergence of this virus, including the Indonesian capital market. This research aims to find out the impact of the number of Covid-19 cases on share prices and profitability of companies listed in the LQ 45 Index in the 2020-2022 period. This research applies a quantitative approach using secondary data obtained from the official website of the Indonesian Stock Exchange and the internet. Regression analysis was carried out on the 33 companies. The result of this research shows that the number of Covid-19 cases does not have a significant influence on share prices and profitability of companies of the LQ 45 Index.